Quantification of theophylline or paracetamol in milk matrices by high-performance liquid chromatography - Tânia A.P. Fernandes; João P. Aguiar; Ana I. Fernandes; João F. Pinto (Elsevier, 2017)
A simple, accurate and sensitive high-performance liquid chromatography (HPLC) method was developed, validated and applied to the determination of either theophylline or paracetamol in milk-based samples. The method allowed drug quantification in fresh and powdered milk with a relatively short run time of analysis and it was also successfully applied to the quantification of the drugs in solid dosage forms intended for pediatric use. Moreover, the main significant advantages over other published works are the simplicity of the sample preparation, reduced assay time and sample loss. The method meets the International Conference on Harmonization guideline for analytical methods validation regarding specificity, linearity, accuracy, precision, specificity and robustness as required by health authorities and applied by industry while designing and marketing new drug products. The technique encompasses the separation of the analytes with a reverse phase C18 column under isocratic conditions and UV detection at 272 nm and 243 nm, respectively, for theophylline and paracetamol. The lower limit of quantification for both drugs was determined as 0.2 µg/mL and the between-batch accuracy was approximately 99.7%. This HPLC method allows quantification of theophylline and paracetamol in milk matrices and it can be applied in the design, development and production of milk-based pediatric dosage forms. Keywords: Liquid chromatography, Fresh milk, Powdered milk, Paracetamol, Theophylline